2017
DOI: 10.1007/s00415-017-8507-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of epilepsy surgery in tuberous sclerosis complex

Abstract: Approximately 50% of patients with tuberous sclerosis complex (TSC) present intractable epilepsy, and surgery is an option for those patients. Hereby, we analyze long-term seizure control and neuropsychological outcomes of epilepsy surgery in patients with TSC. Clinical data were retrospectively collected from 66 patients with TSC and epilepsy followed up over 5 years, 51 of whom underwent epilepsy surgery between 2001 and 2011. Reductions in the number of seizures were analyzed at 1-year (1FU), 5-year (5FU), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 30 publications
6
67
0
Order By: Relevance
“…25 The number of patients not controlled on treatment at baseline was much lower in our study (infantile spasms, 15.5%; focal seizures; 38%) than the 62.5% reported in a previous study by Chu-Shore et al 1 This lower number of treatmentresistant patients could be explained by the earlier diagnosis age shown by the high number of young patients enrolled in our study and by the fact that patients were diagnosed and managed in specialized reference centers that follow established recommended guidelines. 32 The correlation between intellectual ability and seizure control in TSC has been reported. The recommendations of serial EEG studies before clinical seizures have allowed the detection of some patients with subtle or infraclinical seizures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 The number of patients not controlled on treatment at baseline was much lower in our study (infantile spasms, 15.5%; focal seizures; 38%) than the 62.5% reported in a previous study by Chu-Shore et al 1 This lower number of treatmentresistant patients could be explained by the earlier diagnosis age shown by the high number of young patients enrolled in our study and by the fact that patients were diagnosed and managed in specialized reference centers that follow established recommended guidelines. 32 The correlation between intellectual ability and seizure control in TSC has been reported. The recommendations of serial EEG studies before clinical seizures have allowed the detection of some patients with subtle or infraclinical seizures.…”
mentioning
confidence: 99%
“…30,31 This might be the main limiting factor for epilepsy surgery but should be a reminder to refer patients with pharmacoresistant epilepsy early on to expert epilepsy surgery centers to define the possibility of such therapy that is showing fair results, even in patients with multiple foci. 32 The correlation between intellectual ability and seizure control in TSC has been reported. [33][34][35][36][37] Patients with uncontrolled seizures had a higher rate of intellectual disability compared to those with controlled seizures.…”
mentioning
confidence: 99%
“…After epilepsy surgery, authors have reported rates of seizure freedom (Engel Class I outcome) between 48 and 84% depending on the follow-up interval (Arya et al, 2015;Fallah et al, 2015;Liang et al, 2017;Weiner, 2006;Zhang et al, 2013). An extensive presurgical evaluation is carried out and each patient is discussed at a multidisciplinary conference to determine surgical candidacy.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…An extensive presurgical evaluation is carried out and each patient is discussed at a multidisciplinary conference to determine surgical candidacy. After epilepsy surgery, authors have reported rates of seizure freedom (Engel Class I outcome) between 48 and 84% depending on the follow-up interval (Arya et al, 2015;Fallah et al, 2015;Liang et al, 2017;Weiner, 2006;Zhang et al, 2013). Positive predictors of seizure freedom after surgery include younger age at seizure onset, greater extent of resection, focal EEG abnormalities, EEG and MRI concordance, and the absence of generalized seizures or significant developmental delay (Fallah et al, 2013;Fallah et al, 2015;Zhang et al, 2013).…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Cortical tubers and the perituberal cortex in TSC have long been implicated in the generation of seizures [21][22][23][24][25]. Cortical tubers are characterized by laminar dysorganization, dysmorphic neurons, eosinophilic giant cells, and severe gliosis [26].…”
Section: Introductionmentioning
confidence: 99%